Pro-poor animal improvement and breeding — What can science do? - Rege, J.E.O.; Marshall, Karen; Notenbaert, An Maria Omer; Ojango, Julie M.K.; Okeyo Mwai, Ally (Elsevier, 2011)
Livestock provide a wide variety of goods and services that generate income and support the livelihoods of millions of poor people in the developing world. Natural and human selections have shaped existing livestock genotypes throughout the estimated 12,000 year history since the first animal domestication. The result, in many production systems in the developing world, is a livestock genotype adapted to its environment and capable of meeting the needs of smallholder farmers. However, this adaptation is unlikely to be optimal and the rapid changes currently affecting the livestock sector, including policy and market changes, movements of germplasm frequently involving the importation of exotic breeds, and the increasing impacts of climate change are affecting the livestock genotype-environment optimum. This is challenging livestock production systems of smallholder farmers. Current challenges include: high rates of loss of the diversity in livestock populations, rapid transformation in smallholder production systems requiring significant changes in genotypes and their management; increased demand for quality and safe foods; increased market competition in a globalizing economy; increased need for complex partnership arrangements in the ever-changing livestock commodity chain; and lack of adaptive capacity to respond to the rapid system changes. Underlying all these is the general lack of strategies for genetic improvement of livestock in smallholder systems and poor livestock infrastructure in developing countries. Opportunities include increased demand for livestock products — and hence potential market opportunities, and new technologies with potential to leap-frog breeding progress in developing countries. This paper analyses options for pro-poor livestock improvement in developing countries, with particular emphasis on the potential role that science – both old and new – will have, from understanding the social underpinnings to innovative technical solutions. It concludes that one of the highest priority interventions for the smallholder systems is the development of innovative approaches for the strategic use of appropriate genotypes from the available range of global breed resources. The analysis strongly suggests that the highest priority ‘breeding intervention’ should be the provision of appropriate genotypes in a sustainable manner, underpinned by a good understanding of what breed resources exist that have demonstrated potential, where else they could be used, and how they would be delivered to smallholders. Efforts to improve/refine breeding skills of smallholders should proceed in parallel. Institutional arrangements and enabling policies are critical for the success in identifying and applying appropriate genetic technologies, improving access to input services and facilitating access to markets in order to translate productivity gains into incomes.